MORPHOLOGICAL AND MORPHOMETRIC CHANGES OBSERVED IN THE THYMUS IN DIABETIC PATIENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
When you consume some food item that contains carbohydrates, your body turns it into glucose and takes help from Insulin to transport it to different tissues through the bloodstream. Insulin is one of the hormones that the pancreas produces. In most cases, diabetes mellitus can result in devastating complications if left untreated. For almost all types of this disease, insulin is recommended. Diabetes is due to either t he pancreas not producing enough insulin, or the cells of the body not responding properly to the insulin produced.